Beyond cloud infrastructure services in medium size manufacturing - Josephng, P.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
The hyper competitiveness of medium size enterprise is not only heavily dependent on its cloud computing infrastructure evolution but also on its adaptation for sustainability for global web interconnection ecosystems. While the bigger multinationals have experienced positive business values due to their economies of scales, the medium size enterprises still face greater challenges. We contest the view on two similar but evolved theoretical perspectives from Harvard University: Commodity of IT infrastructure and Disruptive Technology into a catalyst model for optimum technology skimming. This paper proposes the establishment of a new dynamic barebones yet optimized cloud infrastructure that will integrates the client server into the IaaS to form an extended Exostructure environment. A 3-stage primary data collection procedure used in the study has consistently validated our findings. Our result suggests that enterprise should continue to invest in optimized IT infrastructure despite the economic turbulence for competitive gearing into the future. Â© 2015 IEEE.